2020
DOI: 10.1584/jpestics.d19-066
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory substances contained in calcium carbonate wettable powder on the oviposition of the peach fruit moth, <i>Carposina sasakii</i>

Abstract: Spraying a calcium carbonate suspension "White Coat" on the fruit of apples significantly suppresses the oviposition of the peach fruit moth, Carposina sasakii. In gas chromatography (GC) with an electroantennographic detector analysis, adult female antennae showed responses to three compounds that were identified as 2,2,4-trimethyl-1,3-pentanediol diisobutyrate (TXIB) and its two mono-hydrolyzed analogs, texanols (1-and 3-isobutyrates), all added as a plasticizer to the agents. An oviposition-choice test usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…in sweet oranges. The oviposition of the peach fruit moth, Carposina sasakii Matsumura, was similarly reduced by spraying calcium carbonate suspension on fruits ( Kazama et al, 2020 ). Calcium carbonate was discovered to significantly reduce the population of mealy bugs infesting bananas ( Geococcus spp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in sweet oranges. The oviposition of the peach fruit moth, Carposina sasakii Matsumura, was similarly reduced by spraying calcium carbonate suspension on fruits ( Kazama et al, 2020 ). Calcium carbonate was discovered to significantly reduce the population of mealy bugs infesting bananas ( Geococcus spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Talc powder, under dry condition, can provide a slick surface for adult black vine weevils, Otiorhynchus sulcatus ( F. ), preventing them from climbing, according to a study ( Bomford & Vernon, 2005 ). A recent study also showed that calcium carbonate applied to apple fruits stopped the peach fruit moth C. sasakii from climbing up or settling on the fruits ( Kazama et al, 2020 ). Similarly, Salerno et al (2020) found that kaolin nanoparticle film significantly impacted the attachments of the Southern green stink bug Nezara viridula and the Mediterranean fruit fly C. capitata .…”
Section: Discussionmentioning
confidence: 99%